Balancing the Scales: Strategies and Challenges of Women Workers Managing Dual Roles in Manufacturing Industries - Maharani, Monica Awalia; Arsi, Antari Ayuning (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
The increasing presence of women in a manufacturing industry, highlights a significant shift in traditional gender roles while underscoring the challenges of balancing domestic responsibilities and professional obligations. This study investigates the dual-role conflicts experienced by female workers and explores the strategies they employ to achieve balance. Using a qualitative approach with a case study methodology, the research delves deeply into the dual-role phenomenon. Data were collected through observations, interviews, and documentation, utilizing purposive sampling for informant selection. Data validity was ensured through triangulation and analyzed using the Miles, Huberman, and Saldana model. The study identifies two primary dimensions of conflict: time-based conflict and pressure-based conflict. Female workers implement five strategies to manage these conflicts: coping mechanisms for stress relief, leveraging social support from family and colleagues, effective time management through prioritization, ensuring meaningful quality time with family, and delegating domestic responsibilities to their children and spouses. However, the effectiveness of these strategies is often hindered by inconsistent delegation and insufficient support from the company and colleagues. The study concludes that enhanced support from both family and the workplace is essential to help female workers achieve a sustainable balance between their personal and professional lives.